Nora and the great bear - Krause, Ute. (New York : Dial Books for Young Readers, 1989)
Nora learns to hunt and dreams of capturing the fabulous Great Bear, until she becomes lost in the forest and it appears to help her.
School Library Journal.
Booklist.
Horn Book.
3.2
K-3
Keywords: Bears -- Fiction; Hunting -- Fiction; Bears -- Fiction; Hunting -- Fiction; Bears -- Fiction; Hunting -- Fiction